Pers Baru dan Restorasi Fungsi Pers sebagai Media Kontrol Sosial di Indonesia dalam Perspektif Demokrasi - Muhammad Muslimin; Febrian Febrian; Mada Apriandi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
A state is said to be democratic if it provides a neutral public space for all citizens to express their opinions and ideas, including criticizing injustices committed by those in power. The purpose of this study is to describe, from a democratic standpoint, the restoration of the function of the press as a medium of social control in Indonesia, particularly in the context of the new press. A normative approach was used in this study’s research method. The study’s findings indicate that the new internet-based press can help to restore the function of the press as a medium of social control in a democratic context. The new press’s cyber public space can provide guarantees and expand public participation in all aspects of government and state life. The cyber public space, which is technically public and is linked to the National Cyber Parliament via the national press website, will serve as media control for the government so that it does not abuse its authority.